Aplikasi Jaringan Syaraf Tiruan Backpropagation dalam Prediksi Curah Hujan Bulanan di Kabupaten Wajo Sulawesi Selatan - Fitriyanti, Fitriyanti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Prediction method is an estimate of what will happen based on data patterns obtained from an event that has passed. One method that can be used to predict is an artificial neural network (ANN). This study aims to determine the results of monthly rainfall by looking at the results of the validation value of the Backpropagation Neural Network method. Data processing using octave software. The results obtained in the form of graph patterns of predictions and actual data. Validation based on Root Square Mean Error (RMSE) using the Backpropagation method for the Sakkoli, Paria/Majennang and Anabanua rain posts has a value of 0.150., 0.107 and 0.024